Prolegomenon for an ethics of visibility in Hannah Arendt - Bethânia Assy (Kriterion, 2004)
This paper aims to discuss the Arendtian notions of appearance and perception in order to promote a displacement of those conceptions from the generally associated domain of passive apprehension of the faculty of knowledge towards the domain of a praxiology of action and language, based on an active perception. Arendt's appropriations on the Heideggerian "to take one's place" (sich hin-stellen) will be discussed, as well as the Augustinian "finding oneself in the world" (diligere). A twofold disposition of appearance will be distinguished: producing and position, whose transposed to the Arendtian notion of world correspond, respectively, to fabrication (poiesis) of the world, man's objective in-between space, and to action (praxis) in the world, man's subjective in-between space. Those conceptual replacements, in a broad sense, uphold a closer imbrication between the activities of the mind and acting, stricto sensu, and consequently, foment not only the valorization of the public space, but the visibility of our acts and deeds as well, calling out the dignity of appearance in ethics. Este trabalho tem como objetivo discutir as noções arendtianas de aparência e percepção, a fim de promover um deslocamento dessas concepções do domínio geralmente associado da apreensão passiva da faculdade de conhecimento em direção a uma praxiologia da ação e da linguagem, baseada na percepção ativa. As apropriações de Arendt do "apresentar-se como" (sich hin-stellen) heideggeriano serão discutidas, bem como o "achar-se no mundo" (diligere) agostiniano. Será feita a distinção de uma dupla disposição da aparência: produção e posição, que transpostas para a noção arendtiana de mundo correspondem, respectivamente, à fabricação (poiesis) do mundo, o espaço-entre objetivo do homem, e à ação (praxis) no mundo, o espaço-entre subjetivo do homem. Essas substituições conceituais, em sentido mais amplo, sustentam uma imbricação mais próxima entre as atividades da mente e a atuação, stricto sensu e, conseqüentemente, fomentam não só a valorização do espaço público, como também a visibilidade de nossas ações e feitos, evocando a dignidade da aparência na ética.